(untitled) (Journal of Educational Sciences, 2020)
Domestic violence is one of the most important problems both in the world and in Kazakhstan. The World Health Organization (WHO), governments of different countries, international and national public organizations, the people themselves deal with this problem. Many countries have laws, roadmaps, and strategies to prevent domestic violence. In the field of education, the prevention or elimination of violence against children and abuse is one of the most important priorities. In Kazakhstan, UNESCO is actively working to protect the rights of children. They analyze the situation of Kazakhstani families and children, the situation of children in school and present the results. In our article, compiling our own questionnaire and using it as a research method provides the closest approach to the situation of children. The results of the study once again show the true picture of violence against children. The contradiction lies in the discrepancy between the ideas of children and parents about domestic violence. It is known that the role of social pedagogues in schools occupies a special place in this regard. Nevertheless, a sufficient level of their competence to solve this problem and a specific algorithm of work is an issue that attracts the attention of the education sector. Key words: domestic violence, protection of children’s rights, social educator, algorithm.